Intra-Regional and Global Competitive Dynamics of African Sugar Industries - Joshua MABETA; Lubos SMUTKA (Communications of International Proceedings, 2024)
Recent dynamics in the sugar industry, including price fluctuations in the global market, reforms in the European sugar sector, and changes in intra-regional trade patterns, underscore the need to understand changes in the competitiveness of African sugar exports. This paper, therefore, uses the Normalized Revealed Comparative Advantage (NRCA) index and the Harris-Tzavalis panel-data unit-root test to conduct a comprehensive analysis of the dynamics in both  inter and intra-regional competitiveness of sugar exports across 34 African countries using panel data that spans from 2001-2021. The NRCA indices reveal notable shifts and patterns in the competitive landscape of African sugar exporters. As of 2021, half of the countries under scrutiny demonstrated a competitive edge in sugar exports, representing a slight uptick from the fourteen (14) observed in 2021. Nonetheless, only eight (8) African countries, predominantly from southern Africa, have sustained their competitiveness both globally and intra-regionally over the entire analysis period. The majority of African sugar exports have struggled to maintain competitiveness on the global market, with some alternating between periods of comparative advantage and comparative disadvantage. However, three North African countries, particularly Algeria, Egypt and Morrocco gained comparative advantage during this timeframe. The sustained competitiveness of Southern African countries and the gain in competitiveness of some North African countries highlights the importance and growing influence of Foreign Direct Investment (FDI) in shaping the developmental trajectory of African sugar industries.
Keywords: Intra-regional and global competitiveness; sugar exports; Africa